(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Anastomotic Leakage (AL) is a serious complication after esophagectomy, increasing morbidity, hospital stay, and mortality. Hypoalbuminemia may predict AL, but its early postoperative role is unclear. To assess the association between early postoperative serum albumin and AL in esophageal cancer patients underwent esophagectomy. Materials and methods: In this prospective study, 84 patients with confirmed esophageal carcinoma underwent curative esophagectomy. Serum albumin was measured on postoperative day one. Patients were monitored for AL and other complications. Chi-square, t-test, and multivariate logistic regression were used to identify predictors of AL. Results: Mean age was 55.8 ± 9.1 years, 78.6% were male. AL occurred in 20.2% (17/84). Hypoalbuminemia (<3.5 g/dL) on day one was strongly associated with AL (p < 0.001). Among patients with albumin <2.5 g/dL, 69.2% developed leakage, no AL occurred in patients with albumin ³ 3.5 g/dL. Hypoalbuminemia remained an independent predictor (Adjusted OR: 10.94, 95% CI: 3.12–38.36, p < 0.001). AL patients had longer hospital stays (33.2 ± 11.9 vs. 15.1 ± 7.9 days; p < 0.001). Conclusion: Early postoperative hypoalbuminemia is strongly linked to AL after esophagectomy. Serum albumin on day one may serve as an early biomarker to guide risk stratification and postoperative care. JCMCTA 2025 ; 36 (2) : 35-40